2018
DOI: 10.1016/j.jmapro.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic removal strategy for machine vision assisted scanning micro electrochemical flow cell

Abstract: Small cavities on a sliding surface can improve lubrication performance, which has been verified by many researchers. Electrochemical machining (ECM) is an effective way to fabricate this kind of small cavities on a large scale. When the diameter and the removal volume for the cavities are specified, it is still required to efficiently determine the appropriate machining parameters. This paper presents a machine vision based control system for an ECM variant: the scanning micro electrochemical flow cell (SMEFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Clare et al [15,16] proposed a JEMM method involving a metal nozzle with an adjustable jet angle; it was found that having the electrolyte jet direction form an acute angle with the feed direction resulted in a significantly lower surface roughness, and typical biomedical stent geometries were machined on nickel-based superalloys using this method. Guo et al [17][18][19] researched coaxial aspirated JEMM of stainless steel and plastic mold steel; by rapidly removing the electrolyte outside the central region of the metal-nozzle jet, the stray corrosion on the machined surface of the workpiece was effectively reduced, and machining localization was improved. Ming et al [20,21] researched kerosene-submerged horizontal JEMM of stainless steel; the results indicated that compared to having a vertical metal-nozzle jet, a horizontal one reduced the contact area between the reflected electrolyte and the outer wall of the metal nozzle, and this also increased the thickness of the electrolyte flow film and accelerated the removal of electrolytic products, thereby offering significantly enhanced machining localization.…”
Section: Introductionmentioning
confidence: 99%
“…Clare et al [15,16] proposed a JEMM method involving a metal nozzle with an adjustable jet angle; it was found that having the electrolyte jet direction form an acute angle with the feed direction resulted in a significantly lower surface roughness, and typical biomedical stent geometries were machined on nickel-based superalloys using this method. Guo et al [17][18][19] researched coaxial aspirated JEMM of stainless steel and plastic mold steel; by rapidly removing the electrolyte outside the central region of the metal-nozzle jet, the stray corrosion on the machined surface of the workpiece was effectively reduced, and machining localization was improved. Ming et al [20,21] researched kerosene-submerged horizontal JEMM of stainless steel; the results indicated that compared to having a vertical metal-nozzle jet, a horizontal one reduced the contact area between the reflected electrolyte and the outer wall of the metal nozzle, and this also increased the thickness of the electrolyte flow film and accelerated the removal of electrolytic products, thereby offering significantly enhanced machining localization.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, based on motion detection and feature extraction, the human motion pattern is obtained through analysis. e mapping relationship between video content and action type description is established so that the computer can understand the video [2,3].…”
Section: Introductionmentioning
confidence: 99%